Comparative Analysis of Financial Performance of Conventional Banks and Islamic Banks Listed on the Indonesia Stock Exchange (BEI) - Hasniar, Hasniar; Amir, Amir; Asriani Hasan (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to determine whether there are significant differences in the financial performance of Islamic banking and conventional banking listed on the Indonesia Stock Exchange (IDX) using five financial ratios, namely, Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return on Asset (ROA), Operating Expenses Operating Income (BOPO), and Total Asset Turnover (TATO). The method used in this research is descriptive quantitative. The data analysis technique used is the Independent Sample T-test to see if there is a significant difference between the financial performance of Islamic banking and conventional banking. The results of this study indicate that there are significant differences in CAR and TATO ratios between Islamic banks and conventional banks. While in the ratio of NPL, ROA, and BOPO there is no significant difference between Islamic banks and conventional banks. When viewed based on the average value (mean), the financial performance based on BOPO conventional banks are better than Islamic banks. However, when viewed from the CAR, NPL, ROA, and TATO ratios, the financial performance of Islamic Banks is better than that of Conventional Banks.